Running economy, preferred step length correlated to body dimensions in elite middle distance runners - Brisswalter, J.; Legros, P.; Durand, M. (The Journal of Sports Medicine and Physical Fitness, 1996)
Elite distance runners, who were homogenous in terms of VO2max, were tested under two conditions of work intensity: - high, but submaximal velocity close to usual training speeds and near anaerobic threshold (15 km/h, 78.5% VO2max), and - low submaximal velocity that was very different to usual training speeds (9 km/h, 54.4% VO2max) Many physical dimensions were measured. The relationships of body dimensions and movement economy to slow running velocity were opposite those with fast running velocity. There was no relationship between economy of movement between the two velocities. In essence, what was important and influential in governing performance at slow velocity was either unrelated or had an opposite effect at the higher velocity. Mechanisms of adaptation are different according to the velocity of movement. Specific constraints on variables exist for each individual. Implication: Training effects from one training velocity are not likely to transfer to another velocity. The greater the velocities differ, the more likely it is that factors developed at one speed will affect the other detrimentally.